AB0043 TLR4 inhibition reduces movement-induced nociception and ATF-3 expression in experimental osteoarthritis. (15th June 2017) - Ferreira-Gomes, J; Garcia, MM; Nascimento, D; Almeida, L; Quesada, E; Goicoechea, C; Castro-Lopes, J; Neto, F
Abstract : Background: Toll-like receptor 4 (TLR4) is a pattern recognition receptor involved in the initiation of inflammatory responses to control pathogen infections, but is also a "danger-sensing" receptor that recognizes host-derived endogenous molecules called damage-associated molecular patterns (DAMPs). The role of TLR4 in rheumatic diseases is becoming evident, as well as its potential role as a therapeutic option. Objectives: The aim of this study was to evaluate the effect, both on articular histopathology and pain behaviour, of a TLR4 antagonist (TLR4-A1) on an experimental model of OA. The effect of the TLR4-A1 on the activating transcription factor-3 (ATF-3) signalling pathway was also assessed. Methods: OA was induced in adult Wistar rats through an intra-articular injection of 2mg of sodium mono-iodoacetate (MIA) into the left knee. Control animals received a similar injection with saline. TLR4-A1 (10 mg/kg), synthesized by Dr. Quesada from a compound previously described by the Peri Laboratory (Piazza et al., 2009), was intraperitoneally administered, daily, from days 14 to 28 after OA induction. Under the same procedure a control group of animals received the vehicle. Movement- and loading- induced nociception was evaluated in all animals, by the Knee-Bend and CatWalk tests, before and after TLR4-A1 or vehicle administration, at several time-points. Animals were sacrificed 28 days after OA induction. L3-L5 Dorsal Root Ganglia (DRG) were used for immunohistochemistry for TLR4 and ATF-3, spinal cords were immunoreacted for TLR4 and knee joints were processed for histopathological evaluation. Results: Antagonism by TLR4-A1 significantly reduced the nociceptive behavior of OA animals both in the Knee-Bend and Catwalk tests. The effect was immediately observed 1 day after TLR4-A1 administration, but became more evident 4 days later, maintaining thereafter. No improvement in the cartilage histology was observed. The increased ATF-3 expression observed in DRG of OA animals was significantly reduced by TLR4-A1. On the contrary, TLR4 expression slightly increased after antagonist administration both at DRG and superficial dorsal horn levels. Conclusions: Chronic treatment with TLR4-A1 showed an antinociceptive effect on OA animals, not related to articular histopathological improvement, possibly through an ATF-3 dependent mechanism. References: Piazza M, Rossini C, Fiorentina SD, Pozzi C, Cornelli F, Bettoni I, Fusi P, Costa B and Peri F. Glycolipids and Benzylammonium Lipids as Novel Antisepsis Agents: Synthesis and Biological Characterization. J Med Chem 2009, 52, 1209–1213. Acknowledgements: Granted by FEDER funds through COMPETE – Programa Operacional Factores de Competitividade (FCOMP-01–0124-FEDER-021359) and by National Funds through FCT – Fundação para a Ciência e a Tecnologia (PTDC/SAU-NSC/119986/2010); and by Ministerio de Economia y Competitividad (SAF2012–40075-C02–02). Disclosure of Interest: None declared